2020
DOI: 10.1007/s12254-020-00657-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of comorbidities in elderly cancer patients

Abstract: Summary Comorbidity is common among cancer patients and increases with age. Comorbid conditions potentially affect treatment, therapy outcomes, and survival of people with cancer. This short review aims at presenting the prevalence of comorbidities, to illustrate their impact on elderly persons with cancer and to discuss their assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…The majority of patients in this study, approximately 65%, had mild or moderate comorbidity (CCI score 1–2), although the percentage of patients with high comorbidity (CCI score ≥ 3) increased progressively throughout the study period, an increase that was already observed in the previous decade [ 36 ]. It is known that the prevalence of comorbidities increases with age, making cancer patients more vulnerable [ 25 27 ]. The percentage of male patients aged 80 years or older increased by 8% throughout the study period, while in women, this percentage decreased by 13.4%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of patients in this study, approximately 65%, had mild or moderate comorbidity (CCI score 1–2), although the percentage of patients with high comorbidity (CCI score ≥ 3) increased progressively throughout the study period, an increase that was already observed in the previous decade [ 36 ]. It is known that the prevalence of comorbidities increases with age, making cancer patients more vulnerable [ 25 27 ]. The percentage of male patients aged 80 years or older increased by 8% throughout the study period, while in women, this percentage decreased by 13.4%.…”
Section: Discussionmentioning
confidence: 99%
“…According to data from the Spanish Lung Cancer Group's registry of thoracic tumors, the average age at diagnosis of patients with lung cancer in Spain is 64 years [23]. In the past 50 years, the average age of patients has been increasing progressively [24] along with associated comorbidities [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…al. [5], showed that Comorbid conditions in the elderly (>70 years) resulted in diminished ability to undergo intracavitary brachytherapy. Tumor recurrence and death from cervical cancer were more common in the elderly group.…”
Section: Discussionmentioning
confidence: 99%
“…However, grade 3–4 toxicity is also significantly increased and may not be suitable for frail patients. Surgery may not be an option for those patients because of pre-existing comorbidity and high mortality rate ( 4 , 5 ). In fact, older age by itself is the strongest predictor of non-treatment.…”
Section: Introductionmentioning
confidence: 99%